If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (U + -4)(u + -2) = 0 Reorder the terms: (-4 + U)(u + -2) = 0 Reorder the terms: (-4 + U)(-2 + u) = 0 Multiply (-4 + U) * (-2 + u) (-4(-2 + u) + U(-2 + u)) = 0 ((-2 * -4 + u * -4) + U(-2 + u)) = 0 ((8 + -4u) + U(-2 + u)) = 0 (8 + -4u + (-2 * U + u * U)) = 0 (8 + -4u + (-2U + uU)) = 0 Reorder the terms: (8 + -2U + -4u + uU) = 0 (8 + -2U + -4u + uU) = 0 Solving 8 + -2U + -4u + uU = 0 Solving for variable 'U'. Move all terms containing U to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -2U + -4u + -8 + uU = 0 + -8 Reorder the terms: 8 + -8 + -2U + -4u + uU = 0 + -8 Combine like terms: 8 + -8 = 0 0 + -2U + -4u + uU = 0 + -8 -2U + -4u + uU = 0 + -8 Combine like terms: 0 + -8 = -8 -2U + -4u + uU = -8 Add '4u' to each side of the equation. -2U + -4u + 4u + uU = -8 + 4u Combine like terms: -4u + 4u = 0 -2U + 0 + uU = -8 + 4u -2U + uU = -8 + 4u Reorder the terms: 8 + -2U + -4u + uU = -8 + 4u + 8 + -4u Reorder the terms: 8 + -2U + -4u + uU = -8 + 8 + 4u + -4u Combine like terms: -8 + 8 = 0 8 + -2U + -4u + uU = 0 + 4u + -4u 8 + -2U + -4u + uU = 4u + -4u Combine like terms: 4u + -4u = 0 8 + -2U + -4u + uU = 0 The solution to this equation could not be determined.
| x=-4x+35 | | y=-2y+300 | | 29-2x+5=y | | (8x-4)+(x^2+31)=180 | | (9+z)(4z-7)=0 | | sn=8/n | | k^3-4k^2-19k=0 | | 11.75x^3-49.35x^2+0.1=0 | | 12x^2/3x | | 100Y^2+36= | | (9+z)(-u+9)=0 | | 2^-4x^7/2^3x^-9 | | 6.9x^3=82.4x+1 | | 5(u-4)(-u+9)=0 | | 6.9x^3-82.4x-1=0 | | 13+n=24 | | 2(x+1)=55-2x | | N-4*7=n+1+4 | | 2x(x-2)=264 | | (6+w)(4w-7)=0 | | 3*lnx^2+2=14 | | 4n-1*3=9 | | (-10)+2x=10 | | 3lnx^2+2=14 | | 3/x-1/2x=1/2 | | 22x-2x^3=0 | | -x+y^2=2 | | -7x+7=-3+10 | | 7(p+3)=4(p+6) | | 100Y^2-36= | | (y-11)=0(x-3) | | x^4-6x^2-53=0 |